Novel-activated carbon from waste green coconut husks for the synthesis of biodiesel from pig fat oil blends with tallow seed oil - E.O. Babatunde; S. Enomah; O.M. Akwenuke; T.F. Adepoju; C.O. Okwelum; M.M. Mundu; A. Aiki; O.D. Oghenejabor (Case Studies in Chemical and Environmental Engineering)
In this study, biodiesel was synthesized from blends of pig fat oil (PFO) with tallow seed oil (TSO) in the presence of a novel activated carbon ash (ACA). Pig fat was rendered in a cooker to form pig fat oil (PFO), while the tallow seed was extracted using a Soxhlet extractor. The two oils were blended to achieve a single acidic blend oil. C22H36O3 acid was isolated from cashew nut husk (CNH) and was used to esterify the high-acidity blend oil. The esterified oil was converted to biodiesel in the presence of activated carbon ash (ACA) developed from green coconut husk (GCH). The produced ACA was characterized using proximate and ultimate analysis, AAS, FTIR, SEM, and BET adsorption analysis. The properties of the biodiesel were determined and compared with the recommended standards.Results show that the blends of 70:30 (PFO:TSO) were able to produce an acidic oil. The C22H36O3 acid concentration was titrimetrically obtained as 5.07 M, while the acidic blends oil was reduced to 2.10 mg KOH/g oil. The ultimate and proximate analysis indicated that the GCH ACA was highly rich in carbon with 80.42 % and 85.52 % wt. It was observed that GCH is an exfoliant that absorbed water content in the oil during transesterification. At a reaction temperature of 80 °C, a GCH ACA conc., of 2 % (wt./wt.), a production period of 70 min, and a MOH/EOMR of 1:5.76, the CCRD statistical analysis predicted a value of 98.759 % (wt./wt.). The mean average of 97.672 % (wt./wt.) was obtained after replicate experiments as validated value. The biodiesel that is produced complies with the recommended guidelines. This study suggested that biodiesel production using activated carbon produced from green coconut husks and waste biomass can be referred to as the most economically viable process. The study recommends that other solid waste husks can be harnessed for the synthesis of activated carbon ashes for their applications as catalysts in industries.